2022
DOI: 10.1186/s13578-021-00742-x
|View full text |Cite
|
Sign up to set email alerts
|

Replication and transcription machinery for ranaviruses: components, correlation, and functional architecture

Abstract: Background Ranaviruses (family Iridoviridae) are promiscuous pathogens that can infect across species barriers in poikilotherms and can replicate in amphibian and fish cells and even in cultured mammalian cells. However, as nucleocytoplasmic large DNA viruses (NCLDVs), their replication and transcription mechanisms remain largely unknown. Here, we screened and uncovered the replication and transcription machinery of two ranaviruses, Andrias davidianus ranavirus (ADRV) and Rana grylio virus (RGV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…ADRV 12L and its homologs (such as 95R of frog virus 3, and 102R of Rana grylio virus) have been considered as core genes of iridoviruses and were predicted as Rad2 family proteins, but their functions had not been investigated. In the present study, we cloned and characterized ADRV 12L as a virus encoded protein involved in DNA homologous recombination and repair, and it had been identified as a protein associated with viral nascent DNA in our previous study on the ranavirus replisome and transcription complex [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ADRV 12L and its homologs (such as 95R of frog virus 3, and 102R of Rana grylio virus) have been considered as core genes of iridoviruses and were predicted as Rad2 family proteins, but their functions had not been investigated. In the present study, we cloned and characterized ADRV 12L as a virus encoded protein involved in DNA homologous recombination and repair, and it had been identified as a protein associated with viral nascent DNA in our previous study on the ranavirus replisome and transcription complex [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The total protein was collected at 0, 24, and 48 h post infection (hpi) for Western blot analysis as described above. In addition to the anti-ADRV 12L serum, previously prepared anti-ADRV 85L and anti-ADRV MCP serum [ 20 , 27 ] were used as controls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the intracellular life cycle, virus replication involves not only viral proteins but also host proteins. In a recent study on the replication and transcription machinery of ranaviruses, we identified several viral and host proteins as potential proteins associated with viral nascent DNA by proteomic analysis of ADRV infected cells [ 14 ]. Among them, the host MutS homolog 2 (MSH2) was found but its function in virus infection was unknown.…”
Section: Introductionmentioning
confidence: 99%